ON BOUNDEDNESS OF FRACTIONAL MAXIMAL OPERATOR IN WEIGHTED Lp(.) SPACES - Mamedov, Farman I.; Zeren, Yusuf (ELEMENT, 2016)
In this paper, we derive some sufficient conditions for the boundedness of the fractional maximal operator in the weighted variable exponent Lebesgue spaces L-p(.), where Sawyer's type pair of modular conditions are proposed on a weight functions and it is assumed a local log-regularity and a decay condition on the exponent function p(.).
Keywords: Fractional maximal operator; weighted Lebesgue space; variable exponent; LEBESGUE SPACES; NORM INEQUALITIES; POTENTIALS; CRITERIA; LP(X); Mathematics